A.M. Klein : Part I: Original poems 1926-1934 ; Part II: Original Poems 1937-1955 and Poetry Translations. - Klein, A. M. (University of Toronto Press, 1990)
This collection includes all Klein's poetry, both original works and translations from Hebrew, Yiddish, Aramaic, and Latin. Many of them, coming from all periods of his careers, have never been published.